Compared transit traffic analysis along the NSR and the NWP. - Alexeeva, Olga V.; Meng, Qiang; Lasserre, Frédéric; Zhou, Chuanbei; Têtu, Pierre-Louis (Routledge, Taylor & Francis Group, 2020)
After two decades of media forecasting a fast expansion of transit traffic, to what extent is it expanding along these two Arctic passages? What picture can be drawn of its unfolding? While all of these questions warrant careful analysis and consideration, this chapter focuses on the present state of commercial transit shipping in the Arctic by distinguishing main trends, similitudes and particularities of the Northwest Passage and the Northern Sea Route. First, we introduce the data source and categorization methods as well as the limits these data sets present. Analyses are carried out from four perspectives: 1) cargo type and volume; 2) transit volumes by transit and cargo types and ship flag; 3) origin and destination of transits; and 4) ships size type.